Evaluation of the Orobua settlement as a historical heritage in West Sulawesi, Indonesia. Issue 3 (4th May 2023) - Bura, Pascarianto; Ando, Tetsuya
ABSTRACT: Traditional houses and villages are a cultural asset of the West Sulawesi region and should be passed down to future generations to preserve the community's identity. The Orobua settlement, located in Mamasa Regency, West Sulawesi Province, is a settlement that had maintained its traditional landscape until the 1990s. However, since the mid-2000s, most traditional houses have either been modified or replaced with modern ones. This paper examines the cultural heritage of the Orobua settlement and suggests strategies to preserve its traditional landscape. Source data were obtained through a literature review, field survey, and interviews with residents.